Mitochondrial and apicoplast genome copy abundances of haemosporidian parasites are explained by host species and parasitic lineage - Brandler, Tim; Chakarov, Nayden (Frontiers in Ecology and Evolution, 2024)
Endosymbiotic organelles, such as mitochondria and plastids, contain own remnant genomes, (nucleoids) whose variable abundance in cells may be adaptive to the physiological necessities and functions of the cells. Unicellular apicomplexan parasites contain one mitochondrium and one apicoplast with variable genome copy numbers. We measured the abundance of michondrial, apicoplast and nuclear genome copies in a set of avian blood samples infected with haemosporidian blood parasites, belonging to the three main genera Plasmodium, Haemoproteus and Leucocytozoon. We designed general primers suitable for qPCR, amplifying fragments of the mitogenome, plastome and nuclear genomes of avian malaria and related haemosporidian parasites. We measured the amplification of these fragments in 153 samples of 23 avian host species and infected with 33 parasitic lineages. We estimate on average several hundred mitochondrial genome copies and several tens of apicoplast copies per haploid gametocyte cell with substantial variation among samples. Host species appeared to differ in their mitogenome abundance while parasitic lineages differed in plastome abundance per cell (per nuclear copy signal). We did not find consistent differences between parasite genera or higher avian taxa. Parasite lineages and host bird species did not differ consistently in infection intensity, estimated from parasite to host nuclear signals, which may indicate that samples were taken at different stages of infection. However, this and similar results remain to be cross-validated with in-situ imaging techniques. The novel molecular tools introduced here offer avenues for the characterization of nucleoid abundance of haemosporidian parasites over environmental conditions and parasitic developmental stages. Such measures will improve our understanding of parasite physiology, ecology, the coadaptation and coevolution with hosts and suggest possible augmentations to standard methods in the research field.